SVC Is a Marker of Respiratory Decline Function, Similar to FVC, in Patients With ALS - Pinto, Susana; de Carvalho, Mamede (Frontiers in Neurology, 2019)
Introduction: Respiratory function is a critical predictor of survival in amyotrophic lateral sclerosis (ALS). We aimed to determine if slow vital capacity (SVC) is a predictor of functional loss in ALS as compared to forced vital capacity (FVC). Methods: Consecutive ALS patients in whom respiratory tests were performed at baseline and 6 months later were included. All patients were evaluated with revised ALS functional rating scale (ALSFRS-R) and the respiratory tests, SVC, and FVC. Significant independent variables of functional decay were assessed by univariate Kaplan-Meier log-rank test and multivariate Cox proportional hazards model. A monthly decay not exceeding 0.92 in ALSFRS was considered as the time event. Results: We included 232 patients (134 men; mean onset-age 59.1 ± 11.23 years; mean disease duration from first symptoms to first visit: 14.5 ± 12.9 months; 166 spinal and 66 bulbar onset). All variables studied declined significantly between the two evaluations (p < 0.001). FVC and SVC were strongly correlated at study entry (r2 = 0.98, p < 0.001) and FVC and SVC decays between first evaluation and 6 months after were the only significant prognostic variables of functional decay (p < 0.001). Conclusion: FVC and SVC decay are inter-changeable in predicting functional decay in ALS. Pharmacological interventions reducing the decline rate of FVC and SVC can have a positive impact on the global functional impairment, with relevant implications for clinical trials' design and interpretation.